2011
DOI: 10.5710/amgh.v48i1(265)
|View full text |Cite
|
Sign up to set email alerts
|

Nuevo Material Postcraneano deSaurosuchus galileiReig (Archosauria: Crurotarsi) del Triásico Superior del Centro-Oeste de Argentina

Abstract: NEw POSTCRANIAl MATERIAl OF SauroSuchuS Galilei reiG (ARChOSAURIA: CRUROTARSI) FROM ThE lATE TRIASSIC OF CENTRAl-wESTERN ARGENTINA. Saurosuchus galilei Reig is a "rauisuchid" from the Ischigualasto Formation (late Carnian, late Triassic) located in central-western Argentina. This paper is the first detailed description of the proatlas-atlas-axis complex of this taxon, of a complete and articulated vertebral column, and of both scapulae. Overall morphology of the proatlas-atlas-axis complex is similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 33 publications
3
49
0
9
Order By: Relevance
“…There are no signs of articulation facets on the lateral margins, which indicate that the osteoderm originated from a single median row of osteoderms and was not part of a paramedian series. Whereas a paramedian row of osteoderms is found along or attached to the cervical and dorsal vertebrae in rauisuchian archosaurs (Peyer et al 2008;Gower and Schoch 2009;Trotteyn et al 2011), single median rows of symmetrical osteoderms originated from the tail section (Peyer et al 2008). Symmetrical and pointed osteoderms, similar to the one in question, are present in Ticinosuchus ferox from the posterior part of the tail dorsally and ventrally, Prestosuchus chiniquensis (UFRGS-PV0629T), and Rauisuchus tiradentes (Lautenschlager 2008).…”
Section: Caudal Osteodermmentioning
confidence: 92%
See 4 more Smart Citations
“…There are no signs of articulation facets on the lateral margins, which indicate that the osteoderm originated from a single median row of osteoderms and was not part of a paramedian series. Whereas a paramedian row of osteoderms is found along or attached to the cervical and dorsal vertebrae in rauisuchian archosaurs (Peyer et al 2008;Gower and Schoch 2009;Trotteyn et al 2011), single median rows of symmetrical osteoderms originated from the tail section (Peyer et al 2008). Symmetrical and pointed osteoderms, similar to the one in question, are present in Ticinosuchus ferox from the posterior part of the tail dorsally and ventrally, Prestosuchus chiniquensis (UFRGS-PV0629T), and Rauisuchus tiradentes (Lautenschlager 2008).…”
Section: Caudal Osteodermmentioning
confidence: 92%
“…The cervical vertebrae are short and high in Prestosuchus chiniquensis, whereas they are actually considerably longer in ''Prestosuchus'' loricatus 1 (BSPG AS XXV 13). A single cervical vertebra, tentatively referred to Saurosuchus galilei by Sill (1974), is also very elongated (length:height = 3.7:1), but the discovery and recent description of new material, including one complete and several fragmentary cervical vertebrae of Saurosuchus galilei, showed that the respective vertebra described by Sill (1974) did not belong to Saurosuchus galilei, but might possibly belong to another pseudosuchian (Trotteyn et al 2011). The cervicals of Saurosuchus galilei, however, are short and nearly isometric (op.…”
Section: Cervical Vertebraementioning
confidence: 95%
See 3 more Smart Citations